Organization of stroke care in Turkey. Issue 1 (January 2017) - Ince, Birsen; Necioglu, Dilek; ,
Stroke is one of the major health problems in Turkey. Since cerebrovascular disease is the second leading cause of death, institutional organizations are important to decrease the burden of stroke in our country. Although the number of comprehensive stroke centers has been increasing constantly and many significant improvements have been realized in last years, there are still some regions without a comprehensive stroke center in Turkey.